Research on acute toxicity and analgesic activity of a fusion protein of omega-conotoxin mviia and thioredoxin - Binh, Doan Viet; Huyen, Bui Thi; Kim Dung, Nguyen Thi; Bich Thao, Le Thi; Bich Nhi, Nguyen; Chi, Phan Van (Academia Journal of Biology, 2012)
Omega-conotoxin MVIIA (w-CTX) a neurotoxin isolated from the venom of Cone snail Conus magus, is a potent and selective blocker of the N-type voltage-sensitive calcium channel in neurons. Thereby it can inhibit the function of calcium chanel and neurotransmitter receptors, blocks the pain signal propagation to the brain or directly targets nociceptive neurotransmission. w-CTX has been cloned, expressed in the fusion form with thioredoxin (Trx-CTX ) in E. coli in the institute of biotechnology, Ha noi and finally purified. Trx-CTX could be produced in large amount, whereas the synthesis of w-CTX is difficult due to the long synthetic process and low yield. In this paper we present our study on analgesic activity and acute toxicity of Trx-CTX with the aim to test the possibility of the Trx-CTX for medical applications. The experiments were carried out in male mice of Swiss race weighing 20 g. The analgesic activity of Trx-CTX was measured in hot-plate assay. Its acute toxicity (LD50) was determinated by the method described by Behrens and Karber. The results showed that Omega-conotoxin MVIIA in the fusion form with thioredoxin possess an analgesic activity 18 times better than morphin hydrochloride and its LD50 is detected at the dose of 775 µg Trx-CTX/g mouse body weight. Trx-CTX could be used for medicinal purpose.